Determinasi Tingkat Suku Bunga Perbankan di Indonesia - Arief Hadi Putra; Siswoyo Hari Santosa; Regina Niken Wilantari (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
The interest rate has an important role to regulate the exchange rate affecting an economy and banking transactions betweencountries.The interest rate as a trigger factor of development of a country has a very important role to cope with the level ofinflation and the exchange rate in the country. In this study, several factors are considered to influence the interest ratesinclude inflation, and exchange rates. The method used is multiple linear regression with time series data. The study wasconducted using monthly data from July 2005 until December 2012. The results of the regression carried out showed thatindlasi positive and significant impact on interest rates. While the exchange rate and no significant negative effect on interestrates.